Jezični tragovi Kelta u Iliriku - Matasović, Ranko (Array, 2003)
This paper contains a list of Celtic proper names (anthroponyms) found on Latin inscriptions in Illyricum. The Celtic origin of several names is discussed and their distribution is analyzed.